The Law Enforcement of Corruption Crimes in Terms of Authority Abuse - Yasmirah Mandasari Saragih; Tengku Riza Zarzani (International Journal of Law Reconstruction, 2023)
The purpose of writing is to find out and analyze law enforcement in the abuse of authority as a source of corruption. To answer the writing questions that have been formulated above, the authors will use the normative research method. In the legislation regarding the crime of corruption, the element of "abuse of authority" has been regulated and is even part of the core of the corruption offense. In Article 3 of Act No. 31 of 1999 in conjunction with Act No. 20 of 2001 concerning the Eradication of Corruption. Furthermore, the element of "abusing the authority, opportunity or means available to him because of his position or position". Abuse of authority is included as an offense of corruption since the Military Ruler Regulation of l957 until now.